Labor Rights of Minors Under Martial Law in Ukraine - Dubovyk, Kateryna (Theory and Practice of Public Administration, 2023)
In this article, the main attention is paid to the protection of the labor rights of minors in the conditions of martial law and hostilities that are ongoing in Ukraine, during the hostilities, the Ukrainian labor market lost a quarter of the able-bodied population, who were evacuated abroad. In such a situation, employers are forced to place minors in private enterprises and institutions, compensating for the resources of employees and taking into account the fact that as a result of the de-occupation of the territories, services for children have ceased to function to protect the rights of minors. At the same time, it is necessary to understand all the risks of the post-war labor market and, at the legislative level, create conditions for its stabilization and retention of citizens in their workplaces with respect for guaranteed human rights. This especially applies to minors who already work at Ukrainian enterprises or plan to work for them. Accordingly, it is relevant to study the specifics of ensuring the labor rights of minors under martial law.